The Influence of Clean Water Sources on Toilet Ownership and Waste Processing With Diarrhea Disease Incidence in Toddlers - Penina Gobai; Nur Susan Iriyanti Ibrahim; Gandhi Pratama (Sekolah Tinggi Ilmu Kesehatan Kesdam IV, Diponegoro Semarang, Indonesia, 2024)
Background:Diarrhea is still a health problem and a cause of death in toddlers. Lack of attention to clean water sources, toilet ownership, and waste management can lead to high rates of diarrhea. An initial survey conducted at the Enarotali Health Center from March 2023 to October 2023, the number of diarrhea cases was 78 with a percentage of 47.43%. Objective: to determine the relationship between clean water sources, toilet ownership, and waste management with the incidence of diarrhea in toddlers in the Enarotali Health Center work area. Method: This study is quantitative with a cross-sectional approach conducted at the Enarotali Health Center, Paniai Regency from April to June 2024. Sample selection using the Random Sampling technique was 78 people. Data processing was carried out using SPSS version 16. Results: The results of the study showed that there was a relationship between clean water sources, toilet ownership, and waste management with the incidence of diarrhea in toddlers with a significant value of p-value = 0.00 (p-value = <0.05). Conclusion: There is a relationship between clean water sources, toilet ownership, and waste management with the incidence of diarrhea in toddlers. Suggestion: Researchers hope that mothers of toddlers at the Enarotali Health Center can get clean water sources, healthy toilet ownership, and good and proper waste management to prevent cases of diarrhea in toddlers.